Analysis of User Acceptance Factors in Employee Attendance System - Vebiana, Galuh Roro; Agusdin, Riza Prapascatama (Sistemasi: Jurnal Sistem Informasi, 2023)
The importance of maintaining the quality of information systems is one of the main factors in creating the success of a system owned by a company so as to encourage employees to utilize technology in completing their work. The web-based employee presence system is one of the systems developed by companies to monitor and measure the level of productivity of human resources. Based on the results of interviews conducted by researchers with five informants, it was found that the user's intention to use the system was still relatively low because the user was not satisfied with the implementation of the employee presence system. System evaluation can be carried out to find out what factors have a significant influence on behavioral intentions and the use of the staffing attendance system by adopting the UTAUT 2 acceptance model. This study makes adjustments to the UTAUT 2 model by eliminating price value as an exogenous variable. A total of 291 data were obtained from respondents through distributing questionnaires and data analysis was carried out using the PLS-SEM analysis technique assisted by SmartPLS. The results of the analysis show that system users must first develop behavioral intentions to use the presence system by increasing significant factors, namely: performance expectancy, effort expectancy, facilitating conditions, hedonic motivation which is reinforced by gender, habit, and behavioral intention.